2022
DOI: 10.2478/cpp-2022-0005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the most common psychological problems during coronavirus epidemics: A systematic review and meta-analysis

Abstract: Introduction: There have been so far three noteworthy epidemics caused by coronaviruses: SARS, MERS, and COVID-19. We aimed to review prevalence of the most common psychological problems during these epidemics. Material and methods: We conducted systematic reviews and meta-analyses of studies. A comprehensive search was performed in electronic databases PubMed/MEDLINE, Web of Science, PsycINFO/ProQuest, SCOPUS, and Google Scholar. Two independent reviewers searched for all Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Both surveys showed the lowest ratings related to illness coherence, reflecting the ability to make sense of and cope with the pandemic. These findings suggest that mental representation of COVID-19 changed in some ways, and what is common to our results and those reported by others is the increase in knowledge about COVID-19, stronger sense of negative emotions and consequences of COVID-19 after several waves of the pandemic [4,31,[33][34][35][36]39]. Our findings are consistent with results reported in a longitudinal study [24], which showed that the highest level in the hierarchy of COVID-19 representations was occupied by a sense of negative consequences, while the lowest level was occupied by sense of personal control.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Both surveys showed the lowest ratings related to illness coherence, reflecting the ability to make sense of and cope with the pandemic. These findings suggest that mental representation of COVID-19 changed in some ways, and what is common to our results and those reported by others is the increase in knowledge about COVID-19, stronger sense of negative emotions and consequences of COVID-19 after several waves of the pandemic [4,31,[33][34][35][36]39]. Our findings are consistent with results reported in a longitudinal study [24], which showed that the highest level in the hierarchy of COVID-19 representations was occupied by a sense of negative consequences, while the lowest level was occupied by sense of personal control.…”
Section: Discussionsupporting
confidence: 89%
“…A negative emotional representation of COVID-19 may be associated with better compliance, but it may also perpetuate or even exacerbate mental health problems [34,38]. The increased confidence that the viremia can be controlled through medical interventions may be linked to the widely promoted knowledge related to COVID-19; it also reflects changes in Polish people's awareness related to the symptoms, diagnosis and treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation